Lupine, a source of new as well as hidden food allergens - Jappe, Uta; Vieths, Stefan (Molecular nutrition & food research, 2010)
The present review summarizes current knowledge about lupine allergy, potential sensitization routes, cross-reactions between lupine and other legumes, and the respective IgE-binding proteins. Since the 1990s, lupine flour is used as a substitute for or additive to other flours, mostly wheat flour, in several countries of the EU. In 1994, the first case of an immediate-type allergy after ingestion of lupine flour-containing pasta was reported. Since then, the number of published incidents following ingestion or inhalation of lupine flour is rising. So far, the Lupinus angustifolius β-conglutin has been designated as the allergen Lup an 1 by the International Union of Immunological Societies Allergen Nomenclature Subcommittee. Initially, publications focussed on the fact that peanut-allergic patients were at risk to develop anaphylaxis to lupine due to cross-reactivity between peanut and lupine. At present, however, the ratio between cases of pre-existing legume allergy (mostly peanut allergy) to de novo sensitization to lupine seed is nearly 1:1. Although in December 2006, lupine and products thereof were included in the EU foodstuff allergen list according to the Commission Directive 2006/142/EC amending Annex IIIA of Directive 2000/13/EC in order to prevent severe reactions caused by “hidden food allergens”, the majority of patients and medical personnel are still not aware of raw lupine seed as potentially dangerous food allergen.
Gesehen am 18.07.2023